Evaluasi Kinerja Perawat dalam Pemberian Asuhan Keperawatan end of life Rumah Sakit X di Jakarta - Teresa Teresa; Hanny Handiyani; Dewi Gayatri (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2021)
Evaluating the performance of nurses in providing end-of-life care among nurses in the government hospital in JakartaBackground: The application of end-of-life nursing care has not been optimal. The effect on nursing performance. These factors include liking civil servants, attitude, and leadership.Purpose: To find out the determinants of nurse performance that must be done in the final period of nursing care in the hospital.Method: A quantitative-based cross-sectional with the population and sample are staff nurses at Jakarta Hospital. The samples taken with purposive sampling method (220 nurses). Analyzing by correlation’s chi square and logistic regression.Results: Finding that there was a relationship between nursing performance and employment status (p-0,018), attitude (p-0,000), and leadership (p-0,044). Multivariate result show nursing performance has a relationship with employment status (p-0,004), attitude (p-0,978) and leadership (p-0,855).Conclusion: Nursing performance related to job status, attitude, and leadership has a strong relationship. Suggestions to hospital management to support nurses attending workshops or training in stimulating nursing behavior and leadership related to patient care in end-of-life nursing performance and following by rewards in employment status.Keywords: Evaluating; Performance of nurses; Providing end-of-life care; Nurses; HospitalPendahuluan: Penerapan asuhan keperawatan pasien end of life belum optimal. Hal ini dapat dipengaruhi oleh kinerja perawat. Faktor-faktor yang mempengaruhi kinerja perawat adalah status kepegawaian, sikap, dan kepemimpinan. Tujuan: Mengetahui kinerja perawat dalam menerapkan asuhan keperawatan end of life di RS.Metode: Metode penelitian yang digunakan adalah penelitian kuantitatif cross sectional. Populasi dalam penelitian ini adalah perawat pelaksana yang bekerja di rumah sakit X di Jakarta. Tehnik pengambilan sampel yang digunakan dengan purposive sampling sebanyak 220 perawat pelaksana. Analisis dilakukan dengan uji chi square dan regresi logistic.Hasil: Menunjukkan ada hubungan yang bermakna antara kinerja perawat dengan status kepegawaian (p-0,018), sikap (p-0,000), dan kepemimpinan (p-0,044). Hasil multivariat menunjukkan adanya hubungan antara kinerja perawat dengan status kepegawaian (p-0,044), sikap (p-0,978), dan kepemimpinan (p-0,855).Simpulan: Kinerja dalam kategori baik bila status kepegawaian baik, sikap positif, kepemimpinan dijalankan dalam mengarahkan perawat pada penerapan asuhan keperawatan EOL. Saran dibutuhkan pembinaan sikap, kepemimpinan dan perlunya peningkatan status kepegawaian bila memungkinkan.